Elevated visceral adiposity index linked to improved cognitive function in middle-aged and elderly Chinese: evidence from the China health and retirement longitudinal study - Zeng, Zhaohao; Huang, Kunyu; Cen, Yanmei; Jin, Wen; Shen, Yingao; Xiong, Lijiao; Mao, Fengju; Hong, Guo; Luo, Yu; Luo, Xiaoguang (Frontiers in Aging Neuroscience, 2023)
Objected: Cognitive decline and obesity are major global public health issues, and their association has been widely acknowledged. The link between the visceral adiposity index (VAI) and cognitive function in the Chinese population remains uncertain. This study aims to investigate the effects of VAI levels on cognitive function in the Chinese middle-aged and elderly population. Methods: We analyzed longitudinal data from the China Health and Retirement Longitudinal Study (CHARLS) collected in 2011, 2013, 2015, and 2018. VAI levels were divided into three tertiles. Generalized estimating equation (GEE) models were used to explore the relationships between VAI levels and cognitive function, including overall cognitive scores, episodic memory, and mental status. Adjustments were made for potential confounders. Results: The study consisted of 2,677 participants. Contrary to expectations, higher VAI levels were associated with higher overall cognitive scores and improved episodic memory scores, while no significant effect was observed on mental status. The GEE models consistently indicated that higher VAI levels were associated with higher overall cognitive scores, primarily due to their association with episodic memory. Stratified analyses revealed that the VAI was associated with better cognitive function primarily in males, individuals under 60 years old, those with lower education levels, rural residents, and married individuals, mainly in relation to episodic memory. No significant interactions were observed between VAI and demographic factors. Conclusions: Our findings suggest that higher visceral adiposity is associated with slower cognitive decline in the Chinese middle-aged and elderly population, especially in its association with episodic memory. These results underline the need to further investigate the potential protective role of visceral fat in cognitive function, potentially offering new insights for interventions to enhance cognitive function and prevent dementia in this population.